Implementasi Model Pembelajaran Kelompok dalam Mengembangkan Kemampuan Membaca Pada Anak Usia Dini di Tk Muslimat III Durbuk Pademawu Pamekasan - Rasidi Rayhan; Nurul Qomariyah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This study aims to determine the extent to which teachers apply the group learning system in TK Muslimat III. This research method is qualitative with a descriptive type of research. To get the maximum data, researchers use research. The research location is TK Muslimat III Durbuk Village, Pademawu District, Pamekasan Regency. The source data obtained by the researcher comes from primary data through teachers and students, while secondary data is obtained from some scientific works, for example; books, journals, and magazines. By using data collection techniques in the form of interviews, observations, and documentation. As for data analysis, researchers narrate in the form of descriptions. The results showed that: first, the implementation of a group learning system in improving children's reading ability, children were grouped into 4 people according to the level of child reading development, reading books in turns, stimulating children with conversational and question and answer methods. With group learning, children are more enthusiastic and focused because there is a sense of community and foster a hone and compassionate attitude towards students. Second, the supporting factors for the implementation of the group learning system in improving children's reading skills in Muslimat III Kindergarten are that the learning room is packaged so that students are more interested, learning media that attracts students to learn comfortably. Meanwhile, the inhibiting factors of the group learning system in improving children's reading skills in TK Muslimat III are children's lack of interest in listening and listening, lack of obedience, frequent disturbing of friends and lack of interaction between one child and another.